Trying to See the Forest through the Trees: Deciphering the Nature of Memory Immunity to Mycobacterium tuberculosis - Orme, Ian M.; Henao-Tamayo, Marcela I. (Frontiers in Immunology, 2018)
The purpose of vaccination against tuberculosis and other diseases is to establish a heightened state of acquired specific resistance in which the memory immune response is capable of mediating an accelerated and magnified expression of protection to the pathogen when this is encountered at a later time. In the earliest studies in mice infected with Mycobacterium tuberculosis memory immunity and the cells that express this were definable both in terms of kinetics of emergence, and soon thereafter by the levels of expression of markers including CD44, CD62L, and the chemokine receptor CCR7, allowing the identification of effector memory and central memory T cell subsets. Despite these initial advances in knowledge, more recent information has not revealed more clarity, but instead has created a morass of complications – complications that, if not resolved, could harm correct vaccine design. Here, we discuss two central issues. The first is that we have always assumed that memory is induced in the same way, and consists of the same T cells, regardless of whether that immunity is generated by BCG vaccination, or by exposure to M.tuberculosis followed by effective chemotherapy. This assumption is almost certainly incorrect. Secondly, a myriad of additional memory subsets have now been described, such as resident, stem cell-like, tissue specific, amongst others, but as yet we know nothing about the relative importance of each, or whether if a new vaccine needs to induce all of these, or just some, to be fully effective.